Antithyroid antibody (TPO-Ab) Status in Type 2 Diabetic Patients - Alo, Kamrunnahar; Safayet Ahammed; Mahboba Rahman; Shyamal Chandra Banik; Kazi Shihab Uddin (KYAMC Journal, 2023)
Background: Presence of thyroid peroxidase antibody (TPO-Ab) in type 2 diabetic patients is a risk factor for future development of thyroid dysfunction. Objective: To observe thyroid antibody status in type 2 diabetic patients. Materials & Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2016 to June 2017. Total 60 subjects including male and female, age ranged from 40 to 60 years were included in this study, among them 30 were non-diabetic subjects and 30 were type 2 diabetic patients. Results: In this study, mean serum TPO-Ab level was significantly (<0.01) higher in diabetic subjects in comparison to that of apparently healthy non-diabetic subjects and mean serum TPO-Ab level was higher in uncontrolled diabetic subjects in comparison to that of controlled diabetic subjects but the difference is not statistically significant. However, On the other hand, among the diabetic patients 6.67% had positive TPO-Ab whereas, among the uncontrolled diabetic patients 11.76% had positive TPO-Ab. There was no correlation between TPO-Ab and HbA1c. Conclusion: The present study reveals that TPO-Ab may present in type 2 diabetic patients. KYAMC Journal Vol. 14, No. 01, April 2023: 35-38